Synergistic effect on flexural properties of kenaf-glass hybrid composite - Afdzaluddin, Atiqah; Maleque, Md. Abdul; Iqbal, Mohammed (Trans Tech Publications, Switzerland, 2013)
This paper presents the synergistic effect on flexural properties of kenaf-glass (KG) mat reinforced unsaturated polyester (UPE) hybrid composite which can compounded using sheet molding compound (SMC) process. The matrix is kept constant with 70 % volume fraction while kenaf and glass fibers were varied, such as 7.5/22.5 v/v, 15/15 v/v and 22.5/7.5 v/v. The 30 % kenaf and 30 % glass are also used for the preparation of composite materials. The kenaf mat was treated with 6% sodium hydroxide (NaOH) diluted solution for 3 hours. This mercerization process improved the interface by interacting with both the fiber and its matrix. The flexural test was performed using ASTM D790-03 standard. The study showed with the addition of kenaf and glass mat 15/15 v/v, the optimum flexural properties was obtained compared to other composition. This can be concluded that 15/15 v/v KG mat reinforced unsaturated polyester hybrid composite is the most appropriate hybrid composite which can be considered for many engineering structural applications mainly in automotive panel, bottom structure and bumper beam.